1988
DOI: 10.1002/ffj.2730030206
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors affecting the oil composition of some Mentha species grown in north west Italy

Abstract: The chemical composition of eleven mint species, grown in Piedmont (North West Italy) in 1985 and 1986 were studied in relation to environmental factors. Thermoperiod and rainfall were measured and correlated with qualitative and quantitative oil composition changes. Temperature and rainfall changes were found to affect the oil composition of some of them, particularly peppermint. The degree of adaptation and some genetic considerations were also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…Maffei compared the quantity of the main components in an essential oil of peppermint in two different vegetation season. He described the increased quantity of limonene, menthone and menthyl acetate in the season with lower temperatures and high sum of precipitation along with the decrease of the main component, menthol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maffei compared the quantity of the main components in an essential oil of peppermint in two different vegetation season. He described the increased quantity of limonene, menthone and menthyl acetate in the season with lower temperatures and high sum of precipitation along with the decrease of the main component, menthol.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of temperature on different species of mint was studied many years ago . Only one study, however, reported the correlation between the qualitative and quantitative changes in essential oil of peppermint and environmental factors, showing that temperature and rainfall changes affect the oil composition . On the other hand, a good‐quality peppermint oil is characterized by a high content of menthol and low menthofuran at harvest .…”
Section: Introductionmentioning
confidence: 99%
“…En la literatura científica existe solo un reporte acerca del análisis de la composición química del AE de L. ovatus realizado por De Bernardi et al (1990) quienes indicaron la presencia de los compuestos -patchouleno, -cariofileno y humuleno, los cuales difieren de los encontrados en este estudio. Los componentes de los aceites volátiles pueden variar según el clima, tipo y manejo de suelo, luz solar, temperatura y humedad de diferentes ecosistemas (Maffei, 1988;De Almeida et al, 2009;Ghelichnia, 2018). Las investigaciones sobre la composición del AE de especies del género Lasiocephalus son escasas.…”
Section: Discussionunclassified
“…Published information on peppermint oil, obtained from cultivated plants of various origin, indicates that it is characterized by the presence of oxygenated p-menthane monoterpenes such as I-menthol (20-54%), I-menthone (5-43%), menthofuran (1-8%), menthyl acetate (1-29%), and their relatives like isomenthol, isomenthone, neomenthol, neoisomenthol, isomenthyl acetate, neomenthyl acetate, and neoisomenthyl acetate (Lawrence 1978;Chialva et al 1982;Wilkins et al 1982;Kjonaas and Croteau 1983;Katsiotis et al 1985;Gilly et al 1986;Srinivas 1986;Gasic et al 1987;Maffei and Sacco 1987;Udyanskaya et al 1987;Maffei 1988b). Wild-growing M. x piperita plants have higher content of menthofuran (6-24%) than the commercial peppermint oil (Kokkini 1983).…”
Section: Oils Rich In Pule Gone Menthone and Isomenthonementioning
confidence: 99%